Sustainable biobutanol production from pineapple waste by using Clostridium acetobutylicum B 527: Drying kinetics study (Bioresource Technology, 2017)
Present investigation explores the use of pineapple peel, a food industry waste, for acetone-butanol-ethanol (ABE) production using Clostridium acetobutylicum B 527. Proximate analysis of pineapple peel shows that it contains 35% cellulose, 19% hemicellulose, and 16% lignin on dry basis. Drying experiments on pineapple peel waste were carried out in the temperature range of 60-120 degrees C and experimental drying data was modeled using moisture diffusion control model to study its effect on ABE production. The production of ABE was further accomplished via acid hydrolysis, detoxification, and fermentation process. Maximum total sugar release obtained by using acid hydrolysis was 97 g/L with 95-97% and 10-50% removal of phenolics and acetic acid, respectively during detoxification process. The maximum ABE titer obtained was 5.23 g/L with 55.6% substrate consumption when samples dried at 120 degrees C were used as a substrate (after detoxification).